The best and worst of 2019, and hopes and fears for 2020: Part 2. Issue 2 (10th January 2020) - Knopf, Alison
Abstract : Last week's Preview Issue (see ADAW Jan. 6, 2020) didn't have room for all of the past‐year reflections and hopes and fears for the new year from stakeholders. We include them here. Thanks to the field leaders who responded to our request for comments .